Responsibilities of Curators Who Do Not Fulfill Their Obligations to Creditors According to Law Number 37 of 2004 Concerning Bankruptcy and Suspension of Debt Payment Obligations - Yenrizka Gusmaria; Teuku Syahrul Ansari (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Bankruptcy is something that often happens in the business world, it refers to a condition where a debtor is unable to pay his debts to creditors that have matured. Bankruptcy occurs when a debtor has two or more creditors and does not pay off one debt that can be collected.Bankruptcy is defined as a condition where a debtor is unable to fulfill his debt payment obligations, even though the company's financial condition may still be healthy. This is different from bankruptcy where the company experiences major losses and must stop its operations.One case of bankruptcy is PT Ricky Kurniawan Kertapersada (RKK) and the Ministry of Environment and Forestry (KLHK). In the decision of the Commercial Court at the Medan District Court Number 04 / PDT.SUS-PAILIT / 2023 / PN.NIAGA.MDN dated March 21, 2023, the Ministry of Environment and Forestry filed an objection or renvoi procedure which began with the court granting the bankruptcy petition of PT Ricky Kurniawan Kertapersada (RKK).The reason for the bankruptcy petition of PT Ricky Kurniawan Kertapersada (RKK) is the debt to the Ministry of Environment and Forestry (KLHK) to pay for environmental losses and ecological function restoration costs amounting to Rp. 191,803,261,700 for a civil case of forest and land fires based on the decision of the Jambi District Court Number 139 / PDT.G-LH / 2016 / PN.Jmb Jo High Court Decision Number 65 / PDT-LH / 2017 / PT JMB Jo. Supreme Court Decision Number 2145K / Pdt / 2018 dated October 8, 2018 Jo. Supreme Court Decision Number 854PK / PDt / 2022 which has permanent legal force (inkracht van gewijsde). This study aims to analyze an unpublished bankruptcy case and the legal consequences if the curator does not carry out the order in accordance with his obligations, so that the creditor is not included in the Temporary Receivables List (DPS) or the Permanent Receivables List (DPT).